NT-proBNP in patients with out-of-hospital cardiac arrest: Results from the FINNRESUSCI Study. (July 2016) - Myhre, Peder L.; Tiainen, Marjaana; Pettilä, Ville; Vaahersalo, Jukka; Hagve, Tor-Arne; Kurola, Jouni; Varpula, Tero; Omland, Torbjørn; Røsjø, Helge; ,
Abstract: Aim: To assess whether the established cardiovascular biomarker N-terminal pro-B-type natriuretic peptide (NT-proBNP) provides prognostic information in patients with out-of-hospital cardiac arrest due to ventricular tachycardia or fibrillation (OHCA-VT/VF). Methods: We measured NT-proBNP levels in 155 patients with OHCA-VT/VF enrolled into a prospective multicenter observational study in 21 ICUs in Finland. Blood samples were drawn <6 h of OHCA-VT/VF and later after 24 h, 48 h, and 96 h. The end-points were mortality and neurological outcome classified according to Cerebral Performance Category (CPC) after one year. NT-proBNP levels were compared to high-sensitivity troponin T (hs-TnT) levels and established risk scores. Results: NT-proBNP levels were higher in non-survivors compared to survivors on study inclusion (median 1003 [quartile (Q) 1–3 502–2457] vs. 527 [179–1284] ng/L, p  = 0.001) and after 24 h (1913 [1012–4573] vs. 1080 [519–2210] ng/L, p  < 0.001). NT-proBNP levels increased from baseline to 96 h after ICU admission ( p  < 0.001). NT-proBNP levels were significantly correlated to hs-TnT levels after 24 h (rho = 0.27, p  = 0.001), but not to hs-TnT levels on study inclusion (rho = 0.05, p  = 0.67). NT-proBNP levels at all time points were associated with clinical outcome, but only NT-proBNP levels after 24 h predicted mortality and poor neurological outcome, defined as CPC 3–5, in models that adjusted for SAPS II and SOFA scores. hs-TnT levels did not add prognostic information to NT-proBNP measurements alone. Conclusion: NT-proBNP levels at 24 h improved risk assessment for poor outcome after one year on top of established risk indices, while hs-TnT measurements did not further add to risk prediction.